Democratic backsliding and populism: paths for a more productive connection - Ferrari, Ana Laura Rodrigues Ferreira (2021)
This master\'s thesis aims to clarify the connection between democratic backsliding and populism and propose productive paths for the progress of these research agendas. My first research goal is to answer whether the concept of populism adds gains to democratic backsliding studies or whether the costs inherent to this contested concept outweigh them. My second research goal is to suggest how the ideational approach to populism can overcome the limitation of not theorizing about the effects of populism on the quality of democracy. I assess the gains in the concept of populism by investigating three analytical advantages that it could bring to democratic backsliding studies: identifying authoritarian preferences in political actors, recognizing a pattern of institutional change in backsliding processes, and facilitating the unfolding of backsliding processes by legitimating authoritarian measures. After discussing each of these advantages and comparing the patterns of institutional change of a populist (Hungary, 2010-2015) and a non-populist (Bulgaria, 2016-2019) episode of democratic backsliding, I conclude that: identifying authoritarian preferences is a weak analytical advantage of populism; populism does not distinguish the actions chief executives take to erode democracy; and interpreting populism as a legitimating ideology requires that scholars adopt an ideational theoretical strand uncommon in democratic backsliding studies. Therefore, I suggest that scholars interested in democratic backsliding should rethink when and how they should mention populism, as the concept may generate more costs than gains to this research agenda. Finally, I suggest that scholars who adhere to the ideational approach could interpret populism in power as a legitimating ideology and explore how it exerts power in ideas and power through ideas over politicians and voters after elections. Thus, I conclude that, without having to waive its preferred theoretical framework, the ideational approach can expand its reach to embrace the effects of populism on democratic backsliding.